Erosion Potential Based on Erodibility Factors In Cimanggung And Surrounding Region, Sumedang Regency, West Java, Indonesia - Rahmi, Nisa Shafira Muthia; Sophian, Raden Irvan; Khoirullah, Nur; Zakaria, Zufialdi (Faculty of Geological Engineering, Universitas Padjadjaran, 2021)
The research area around Gunung Geulis has been shifted from agricultural land into residential areas. This transformation eventually will affect the water infiltration process especially throughout the rainy season and can cause the intensity of the erosion rate to go higher. Soil erodibility is defined as the susceptibility of the soil to erosion, as the degree to which a soil is easily eroded or not. This research was conducted to determine the erodibility value in an area of ± 25 km2 which administratively belongs to the Districts of Cimanggung and Jatinangor, Sumedang Regency, West Java Province. The erodibility value can be calculated by the method introduced by Wischmeier and Smith (1978) and it is determined based on several parameters, namely texture of the soil, soil structure, permeability value, and organic (%C) content in a soil sample. The research data was obtained by engineering geological mapping of the distribution of surface soil, taking undisturbed soil samples using the hand auger method, and laboratory tests in the form of testing the physical properties of the soil. Then several laboratory tests are conducted to identify the physical properties of soil such as organic (%C) content analysis using Walkley and Black method, grain size analysis, hydrometer analysis, and permeability analysis using the falling head method. In the research area, the soil type is divided into two units, namely the Low Plasticity Silt Unit and the High Plasticity Silt Unit. Soil erodibility values around Gunung Geulis ranged from 0.118 to 0.514 0,1-ton acre hour/acre foot-ton inch which was included in the classification of a low, medium, moderately high, and high erodibility levels according to US customary dimensions.